UMP associates need to emulate leadership of Prophet Muhammad SAW in management of organisation - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 11 November 2022 – Universiti Malaysia Pahang (UMP) associates are called to emulate the leadership and personality of Rasulullah SAW in the management of organisations and families.